Influential Factors Determining Government Expenditure of Lao PDR - PHANLA , Phone; YANGSANSAY , Chahue; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Fiscal Policy has played an important role in Economy development of country. Government expenditure, which is a part of fiscal policy, has been used a policy tool to stimulate economic growth as well as settle various economic problems, financial crisis, Natural disasters and epidemic disease. Therefore, government expenditure is certainly an important issue to studied. The objective of the study is to: 1) government expenditure structure of Lao PDR, 2) influential factors determining government expenditure of Lao P.D.R. which provides quantitative analysis and uses secondary data annually from 1990-2018. It builds Econometrics model and Estimate the Ordinary Least Squares regression method. The result of the study of government expenditure structure of Lao PDR includes government operating expenditures and investment expenditures, which the government expenditures of Lao PDR from 1986-2018 releases that the majority of government operating expenditures could cover 50.77%. Since 1988-2018. The government expenditure in GDP could cover 21.20% on average. And the taxation in government expenditure could cover 46.95%. This figure can infer that government expenditure has change positive according to the economic situation, the financial crisis, natural disasters, the need to develop the nation out of the least developed countries and the people out of poverty. The valiabe expected to be influential factors determining government expenditure of Lao P.D.R consist of four factors such as: 1) changing of gross domestic product (GDP), 2) degree of openness of the economy, 3) changing of money suply(M2), 4) changing of taxation had statistical significance at the level of 0.01. The result also shows that degree of Population and inflation did not determining government expenditure of Lao P.D.R.